SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI TEMPAT KOST UNTUK MAHASISWA DI KOTA SAMPIT - Lukman Bachtiar; Fendy Fendy (Politeknik Bisnis Indonesia, 2023)
The number of students who want to continue their education makes students even leave their hometowns just to get a better education. This can make students look for a temporary place to live while studying or lecturing. There are several factors that make them prefer boarding houses as a temporary residence. A boarding house is a residence that is rented out to other parties with certain facilities at a more affordable price compared to hotels/inns. The number of boarding houses that offer different prices, facilities and have different locations will certainly make students confused in terms of determining the temporary residence they occupy. So, the decision support system by applying the profile matching DSS method is expected to help solve alternative housing problems for students or the general public. And also, with the results of research conducted can show that the profile matching method has good accuracy in providing boarding options for students. From the results of calculations using 5 alternatives, the highest total value or final value is obtained in alternative boarding house 2 with a total value of 9.398.